2005
DOI: 10.1097/01.ccm.0000156786.43935.a0
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillatory ventilation: What large-animal studies have taught us!

Abstract: Background-Much of the information on the physiologic effects, mechanisms of gas exchange, and potential utility of high-frequency oscillation (HFO) has been acquired in animal studies. Specifically, large animal data have been useful in assessing adult application because large animals present many of the same concerns and challenges as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Most of our understanding of HFOV has come from small animal models and the neonatal/pediatric population, and these concepts may not apply to the much larger adult lung. 23 Moreover, in some of these animal studies, potential harmful effects of HFOV were observed. For example, in canine models, significant regional differences were seen in alveolar pressure at various locations in the lungs despite having mean alveolar pressure nearly equal to the mean opening airway pressure.…”
Section: Pathophysiology Considerationsmentioning
confidence: 99%
“…Most of our understanding of HFOV has come from small animal models and the neonatal/pediatric population, and these concepts may not apply to the much larger adult lung. 23 Moreover, in some of these animal studies, potential harmful effects of HFOV were observed. For example, in canine models, significant regional differences were seen in alveolar pressure at various locations in the lungs despite having mean alveolar pressure nearly equal to the mean opening airway pressure.…”
Section: Pathophysiology Considerationsmentioning
confidence: 99%
“…Hypothesized lungprotective effects stem from avoidance of alveolar stretch and cyclic opening and collapse. Since its invention in the early 1980s (2), animal models of acute respiratory distress syndrome (ARDS) have suggested that HFO improves gas exchange, levels of inflammatory markers, and lung histology (3). After clinical experience in premature (4,5) and term neonates (6) and children (7, 8), the use of HFO expanded to adults.…”
mentioning
confidence: 99%
“…Gas exchange during HFOV depends on different mechanisms: interregional gas mixing between units with different time constants (Pendelluft), convective transport attributable to asymmetry between inspiratory and expiratory profiles, cardiac oscillation, collateral ventilation and Taylor dispersion. These mechanisms allow adequate oxygenation and CO2 clearance with tidal volumes of only 1–3 ml/Kg[ 6 , 7 ]. In addition, the raised mean airway pressure can achieve lung recruitment despite unequal time constants, and prevents end-expiratory alveolar collapse[ 8 ].…”
Section: Discussionmentioning
confidence: 99%